Tokoh dan Penokohan serta Nilai Moral dalam Cerita Fabel - Riska Dewi Saputri; Herlina Setyowati (Universitas Mulawarman, 2022)
This study aims to determine (1) characters and characterizations; and (2) moral values ​​in fable stories. This study is a qualitative descriptive study. The source of data in this study is a story entitled